G Protein Pathway Suppressor 1 Promotes Influenza Virus Polymerase Activity by Activating the NF-κB Signaling Pathway - Tomoko Kuwahara; Seiya Yamayoshi; Takeshi Noda; Yoshihiro Kawaoka (mBio, 2019)
ABSTRACT Influenza virus relies heavily on cellular machinery to replicate in host cells. Therefore, to better understand the influenza virus life cycle, it is important to identify which host proteins are involved and how they function in virus replication. Previously, we identified G protein pathway suppressor 1 (GPS1) to be a matrix protein 2 (M2)-interacting host protein. GPS1 is a component of the COP9 signalosome, which regulates the NF-κB signaling pathway. Here, we found that the downregulation of GPS1 expression reduced influenza virus replication by more than 2 log units. Although GPS1 was not involved in the early and late stages of virus replication, such as viral entry, uncoating, assembly, or budding, we found that viral polymerase activity was impaired in GPS1-downregulated cells. Moreover, our results suggest that M2 activates the NF-κB signaling pathway in a GPS1-dependent manner and that activation of NF-κB signaling leads to the upregulation of influenza virus polymerase activity. Our findings indicate that GPS1 is involved in the transcription and replication of influenza virus genomic RNA through the activation of the NF-κB signaling pathway. IMPORTANCE In the present study, we identified G protein pathway suppressor 1 (GPS1) to be a host cellular protein that is important for influenza virus replication. We also found that GPS1 plays a role in viral genome transcription through the NF-κB signaling pathway. Moreover, downregulation of GPS1 also affected the growth of vesicular stomatitis virus. Therefore, GPS1 may be a host target for antiviral drugs against influenza virus and possibly other viruses.